2015
DOI: 10.1371/journal.pone.0129996
|View full text |Cite
|
Sign up to set email alerts
|

Burn Injury Alters the Intestinal Microbiome and Increases Gut Permeability and Bacterial Translocation

Abstract: Sepsis remains one of the leading causes of death in burn patients who survive the initial insult of injury. Disruption of the intestinal epithelial barrier has been shown after burn injury; this can lead to the translocation of bacteria or their products (e.g., endotoxin) from the intestinal lumen to the circulation, thereby increasing the risk for sepsis in immunocompromised individuals. Since the maintenance of the epithelial barrier is largely dependent on the intestinal microbiota, we examined the diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
177
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 223 publications
(197 citation statements)
references
References 54 publications
7
177
1
2
Order By: Relevance
“…Damage to this barrier makes the environment less hypoxic, conducive to aerobic bacterial growth [39,48]. Microbial-derived butyrate stabilizes gut epithelial tight junction proteins, depletes oxygen, and activates/stabilizes HIF-1 in epithelial cells [49,50].…”
Section: Resultsmentioning
confidence: 99%
“…Damage to this barrier makes the environment less hypoxic, conducive to aerobic bacterial growth [39,48]. Microbial-derived butyrate stabilizes gut epithelial tight junction proteins, depletes oxygen, and activates/stabilizes HIF-1 in epithelial cells [49,50].…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that ethanol intoxication exacerbates the suppression of intestinal T cells and potentiates small bowel barrier disruption, and increases Gram-negative bacterial overgrowth within one day after burn injury (8, 9). More recently, we have discovered changes to the microbiome in our rodent model of burn injury directly reflect the changes observed to the microbiome of hospitalized burn patients (10). Microbial dysbiosis and gut leakiness may represent significant confounding factors to post-burn pathogenesis.…”
Section: Introductionmentioning
confidence: 88%
“…Slides were deparaffinized, dried for 25 minutes at 50°C, and then incubated with the indicated probes at a final concentration of 1ng/μl in hybridization buffer (0.9M NaCl, 20mMTris-HCL, pH 7.5, 0.1% SDS) overnight at 50°C in a humidified slide box. Probe sequences were as follows(10): Universal bacterial probe EUB338: Alexa 555 5′-GCTGCCTCCCGTAGGAGT -3′…”
Section: Methodsmentioning
confidence: 99%
“…Real-time PCR analysis using specific primer sets targeting small subunit (SSU) 16s rRNA of total bacteria and Enterobacteriaceae were used to quantify the fecal microbiome as described previously (26). Primer sequences were: 340F (ACTCCTACGGGAGGCAGCAGT) and 514R (ATTACCGCGGCTGCTGGC) for total bacteria, and 515F (GTGCCAGCAGCCGCGGTAA) 826R (GCCTCAAGGGCACAACCTCCAAG) for Enterobacteriaceae (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%